Extension and the Environment: Understanding Florida Residents' Perceptions of Environmental Water-Related Topics: WC167/AEC503, rev. 9/2022 - Warwick, Caroline R.; Lamm, Alexa J.; Warner, Laura A. Sanagorski (EDIS, 2022)
This publication explores Florida residents’ perceptions of a variety of water topics related to environmental issues and their perceived level of importance of each. This resource was developed to help Extension faculty understand Florida residents’ perceptions of water quality and quantity issues so they can better educate this audience and communicate with them about these issues. Additionally, Extension faculty will be able to understand the level of importance the public associates with water issues.